ASALARI OILASINING BIR BUTUNLIGI. ASALARI OILASIDA ONA ASALARINING YAKKA HOKIMLIGI - Jamolov R.Q.; Ma’murova Z. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In the article, worker bees collect nectar and pollen, process nectar and make honey from it during the season. When the work boils, they live 35-45 days. Worker bees that come out in autumn can live up to 5-6 months due to the lack of work. Also, worker bees can never live alone for long, because they are very accustomed to living in a group by instinct, and other processes are reflected.